RELIGIOUS MODERATION ON NU ULAMA’S PERSPECTIVE - Moh. Rivaldi Abdul; Nella Wahyuni (Religi: Jurnal Studi Agama-agama, 2026)
Diversity is reality of being religious in the Nusantara society. Carelessness of this plural reality can bring up the intolerant potency because our failure interlaces interreligious relations in a plural society. This condition makes the narration of Islam Nusantara to be not enough about issues of arts and traditions but also to raise issues about being moderate Muslim in religious diversity. The NU ulamas for a long time have given their interest to the discourse of interreligious relations. This article discussed some teachings of the NU ulamas about practicing Islam in the diversity of Nusantara society. The research method of literature study or library research was used to read NU ulamas’ teachings. Hopefully, this article can present the construction of ideas about being moderate Muslim in religious diversity as an expression of practicing Islam in Nusantara. This article explains that NU ulamas teach the Islamic practice not ignoring consciousness of religious diversity, abolishing the majoritarianism ego, and interlacing relationship of interreligious humanity with other religious people. It is the teaching of NU ulamas about being moderate Muslim in religious diversity. Keywords: Nahdlatul Ulama, Being Muslim, Islamic Knowledge, Islam Nusantara, Interreligious Harmony   Keragaman merupakan realitas beragama dalam masyarakat Nusantara. Pengabaian realitas yang plural ini dapat memunculkan potensi intoleransi, sebab kelalaian kita menjalin hubungan antarumat beragama dalam sebuah masyarakat yang plural. Kondisi ini membuat narasi Islam Nusantara tidak cukup seputar isu seni dan tradisi, namun juga mengangkat isu tentang menjadi Muslim moderat dalam keragaman agama. Para ulama NU, untuk waktu yang lama, telah memberikan perhatian untuk diskursus hubungan antarumat beragama. Artikel ini mendiskusikan beberapa ajaran ulama NU terkait menjalankan Islam dalam keragaman masyarakat Nusantara. Harapannya, artikel ini dapat menghadirkan konstruksi gagasan tentang menjadi Muslim moderat dalam keragaman agama sebagai sebuah ekspresi menjalankan Islam di Nusantara. Artikel ini menjelaskan bahwa ulama NU mengajarkan praktek Islam yang tidak melupakan kesadaran keragaman agama, meruntuhkan ego mayoritanisme, dan menjalin hubungan kemanusiaan antarumat beragama dengan umat agama lain. Demikian itu adalah ajaran ulama-ulama NU terkait menjadi Muslim moderat dalam keragaman agama. Kata Kunci: Nahdlatul Ulama, Menjadi Muslim, Pengetahuan Islam, Islam Nusantara, Kerukunan Antarumat Beragama